Gestión de talento humano y su incidencia en el desempeño laboral del personal de la estación experimental tropical pichilingue del iniap - Velásquez Lucas, Eliana Rocío (2025)
This research was conducted at INIAP's Pichilingue Tropical Experimental Station, which is dedicated to scientific research, innovation, validation, and technology transfer adapted to national production contexts. Recognizing that human talent is a key factor in achieving these institutional objectives, the study aimed to critically analyze the personnel management model and its impact on employee performance. The main objective was to identify the strengths and weaknesses of the current human talent management model, evaluating its efficiency, effectiveness, and alignment with the principles of institutional competitiveness and sustainability. To this end, a mixed-method approach was adopted, combining quantitative and qualitative tools. The design was descriptive and exploratory, supported by a field study that allowed direct observation of the station's internal dynamics. Structured surveys and semi-structured interviews were conducted with different levels of staff: administrative, technical, and agricultural workers, which provided a comprehensive view of the current situation. The results show that, while basic management practices such as induction, training, and performance evaluation exist, these are not yet fully systematized as part of a strategic model. Significant gaps were identified in staff motivation, professional growth opportunities, and effective follow-up to training initiatives. Based on the diagnosis, recommendations are proposed to strengthen the human talent management model, including the design of career plans, evaluation of the impact of training, and the implementation of staff motivation and retention strategies.